Female Psychology in August Strindberg’s The Stronger - Sutandio, Anton; Apriliani, Erica (Bina Nusantara University, 2017)
This research aimed to offer interpretations of August Strindberg’s The Stronger through the lens of female psychology. The Stronger is unique as it seemed very simple yet so intense and powerful with layers of interpretations. Written during 1888-1889, The Stronger, which only had two characters and only one speaking character, had become one of Strindberg’s shortest yet important plays during his career. The female psychology approach used in the analysis would cover the discussion of gender role, women’s self-esteem, competition for males, women’s friendships, ego style, and female psychology. It was an interdisciplinary research that combined structuralist, historical, biographical, and feminist approach to gain a better interpretation on the play. By referring to three different sources on the concept of female psychology, the analysis offered different and interesting interpretations on the nature and dynamics of the two female characters’ relationship. The Stronger has shown an enigmatic attraction in Strindberg’s authorship in which the readers could see the co-existence, collision, conflict, and merge of different paradigms concerning sex, gender, and sexuality.